Regional Economic Outlook, April 2008, Sub-Saharan Africa. (Regional Economic Outlook, 2008)
The region's prospects continue to be promising, but global developments pose increased risks to the outlook. Growth in sub-Saharan Africa should again average about 6 1\2 percent in 2008 with oil exporters leading the way; meanwhile, growth in oil importers is expected to taper off, though only modestly. With food and energy prices still rising, inflation is projected to average about 8 1\2 percent this year for countries in the region, setting aside Zimbabwe. Risks in 2008 are tilted to the downside, but the region is better placed today to withstand a worsening of the global environment.